Preparation method and application of foamed nickel loaded Ru-Ni (OH) 2 electrode with high catalytic performance
By loading Ru-Ni(OH)2 on the foam nickel electrode, an efficient method of removing bromate is achieved, solving the problems of low removal efficiency and high cost in the prior art, and providing a cost-effective electrochemical removal method.
Patent Information
- Application Number
- CN202411661568.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The prior art is difficult to efficiently remove bromate pollution, and traditional electrode materials such as platinum are costly and have few reserves, making it difficult to achieve cost-effective removal methods.
The nickel foamed Ru-Ni(OH)2 electrode is used to load ruthenium through a simple ion exchange method to improve the catalytic performance of the electrode and achieve efficient removal of bromate.
This method improves electron transfer efficiency and H* generation and utilization efficiency, significantly accelerates the removal of bromate, and has simple raw materials, simple synthesis method and low cost.
Smart Images

Figure CN119707036A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysis, and in particular to a preparation method of a nickel foam loaded Ru-Ni(OH)2 electrode and application thereof. Background Art
[0002] Bromate is one of the common disinfection byproducts in drinking water. Due to its potential carcinogenicity and nephrotoxicity, it has been identified as a Class 2B potential carcinogen by the International Agency for Cancer. With the widespread application of ozone pre-oxidation and ozone-bioactivated carbon combined processes in water treatment and remediation processes, the emission of bromate has gradually increased, and the problem of bromate pollution should be given sufficient attention. Bromate is highly stable in water, and exploring a method for efficient removal of bromate is a very meaningful study.
[0003] The World Health Organization stipulates that the content of bromate in drinking water cannot exceed 10μg / L. In order to meet this standard, people have explored methods including filtration, chemical reduction, and biodegradation. However, these methods often have limitations such as high operating costs, secondary pollution, and complex operating procedures. Electrochemical reduction of bromate to bromide is an effective method for treating bromate-containing water, which has the advantages of simple maintenance, fast reaction rate, and no secondary pollution. In the electrochemical reduction of bromate, it mainly uses electrode materials to promote the direct or indirect reduction of bromate. Direct reduction involves bromate acquiring electrons on the electrode surface and being reduced to bromide; while the indirect reduction principle is through the Volmer reaction (H2O+e - =H ad +OH - ) as a key medium. The excellent electrical conductivity, porous structure and high mechanical strength of nickel foam can promote electron transport and catalyst loading. At the same time, atomic hydrogen (H*) is an important medium. The generation of H* in the Volmer reaction is very slow, and precious metal-based composite materials can improve the adsorption and desorption process of atomic hydrogen through optimized electronic structure. Platinum is one of the most effective catalysts for the Volmer reaction, but the cost of platinum is very high and the reserves are small. It is necessary to prepare lower-cost high-efficiency electrodes to solve the pollution problem of bromate. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a nickel foam loaded Ru-Ni(OH)2 electrode with high catalytic performance to achieve efficient removal of bromate. The method uses nickel foam as a substrate and nickel hydroxide as a precursor, and adopts a simple ion exchange method to load ruthenium, thereby preparing a nickel foam loaded Ru-Ni(OH)2 electrode. In order to solve the above technical problems, the present invention provides a method for preparing a nickel foam loaded Ru-Ni(OH)2 electrode with high catalytic performance, comprising the following steps:
[0005] (1) placing the initial nickel foam support in a hydrochloric acid solution with a molar concentration of 3 mol / L and ultrasonically etching it for 10-20 minutes, then taking it out and ultrasonically etching it with ethanol and deionized water for 10-15 minutes respectively;
[0006] (2) the nickel foam in step (1) is placed in a homogeneous solution of nickel nitrate, ammonium fluoride and urea in a mass ratio of 0.466-1.454:0.178-0.556:0.481-1.502, and subjected to a hydrothermal reaction at 90-120° C. for 4-8 hours. After the reaction, the nickel foam is taken out and washed with ethanol and deionized water, and dried at 70° C. for 2-4 hours to obtain a nickel foam loaded with nickel hydroxide;
[0007] (3) Immersing the nickel foam loaded with nickel hydroxide in step (2) in a 0.05-0.60 g / L ruthenium trichloride solution for ion exchange for 2-6 hours, after which the electrode is taken out, washed with water, and dried at 70° C. for 3-5 hours to obtain a nickel foam loaded Ru-Ni(OH)2 electrode.
[0008] Preferably, in step (1), the etching time of the nickel foam carrier in the hydrochloric acid solution is 15-20 minutes.
[0009] Preferably, in step (2), the mass ratio of nickel nitrate hexahydrate, ammonium fluoride and urea is 0.582-1.454:0.223-0.556:0.601-1.502, and the hydrothermal reaction time is 6-8 hours.
[0010] Preferably, in step (3), the concentration of ruthenium trichloride is 0.15-0.60 g / L, and the ion exchange time is 3-6 hours.
[0011] The present invention also provides an application of a nickel foam loaded Ru-Ni(OH)2 electrode. The nickel foam loaded Ru-Ni(OH)2 electrode obtained by the above preparation method can be used for treating bromate-containing wastewater.
[0012] The present invention has the following beneficial effects:
[0013] 1. The raw materials used are simple and the synthesis method is simple.
[0014] 2. By loading Ru-Ni(OH)2 on nickel foam, electron transfer is enhanced, while the generation and utilization efficiency of H* is improved, greatly accelerating the removal of bromate. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the SEM image of Example 4.
[0016] Figure 2 This is the HRTEM spectrum of Example 4.
[0017] Figure 3 The XRD patterns of Example 4 and the comparative example are shown in FIG.
[0018] Figure 4 The cyclic voltammetry curves of Example 4 and the comparative example are shown in FIG. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0020] 1. Examples and Comparative Examples
[0021] Example 1
[0022] (1) A 1 cm*5 cm nickel foam was placed in a 3 mol / L hydrochloric acid solution and ultrasonically etched for 20 minutes, then taken out and ultrasonically etched with ethanol and deionized water for 15 minutes respectively;
[0023] (2) 1.454 g of nickel nitrate hexahydrate, 0.556 g of ammonium fluoride and 1.502 g of urea were weighed and dissolved in 60 mL of deionized water and stirred for 30 minutes, and the nickel foam treated in (1) was added and reacted in a 100 mL reactor at 100° C. for 6 h. After natural cooling, the mixture was taken out, washed with ethanol and deionized water, and dried at 70° C. for 3 hours;
[0024] (3) The product obtained in (2) was cut into a size of 1 cm*1.5 cm, and then placed in a transparent sample bottle containing 20 mL of a 0.15 g / L aqueous solution of ruthenium trichloride trihydrate, and shaken at 270 r / min for 6 hours in an oscillator at 25°C for ion exchange, and then taken out and washed with deionized water, and then dried at 70°C for 4 hours;
[0025] Example 2
[0026] (1) A 1 cm*5 cm nickel foam was placed in a 3 mol / L hydrochloric acid solution and ultrasonically etched for 20 minutes, then taken out and ultrasonically etched with ethanol and deionized water for 15 minutes respectively;
[0027] (2) 1.454 g of nickel nitrate hexahydrate, 0.556 g of ammonium fluoride and 1.502 g of urea were weighed and dissolved in 60 mL of deionized water and stirred for 30 minutes, and the nickel foam treated in (1) was added and reacted in a 100 mL reactor at 100° C. for 6 h. After natural cooling, the mixture was taken out, washed with ethanol and deionized water, and dried at 70° C. for 3 hours;
[0028] (3) The product obtained in (2) was cut into a size of 1 cm*1.5 cm, and then placed in a transparent sample bottle containing 20 mL of a 0.30 g / L aqueous solution of ruthenium trichloride trihydrate, and shaken at 270 r / min for 6 hours in an oscillator at 25°C for ion exchange, and then taken out and washed with deionized water, and then dried at 70°C for 4 hours;
[0029] Example 3
[0030] (1) A 1 cm*5 cm nickel foam was placed in a 3 mol / L hydrochloric acid solution and ultrasonically etched for 20 minutes, then taken out and ultrasonically etched with ethanol and deionized water for 15 minutes respectively;
[0031] (2) 1.454 g of nickel nitrate hexahydrate, 0.556 g of ammonium fluoride and 1.502 g of urea were weighed and dissolved in 60 mL of deionized water and stirred for 30 minutes, and the nickel foam treated in (1) was added and reacted in a 100 mL reactor at 100° C. for 6 h. After natural cooling, the mixture was taken out, washed with ethanol and deionized water, and dried at 70° C. for 3 hours;
[0032] (3) The product obtained in (2) was cut into a size of 1 cm*1.5 cm, and then placed in a transparent sample bottle containing 20 mL of a 0.45 g / L aqueous solution of ruthenium trichloride trihydrate, and shaken at 270 r / min for 6 hours in an oscillator at 25°C for ion exchange, and then taken out and washed with deionized water, and then dried at 70°C for 4 hours;
[0033] Example 4
[0034] (1) A 1 cm*5 cm nickel foam was placed in a 3 mol / L hydrochloric acid solution for etching for 20 minutes, and then taken out and ultrasonicated with ethanol and deionized water for 15 minutes respectively;
[0035] (2) 1.454 g of nickel nitrate hexahydrate, 0.556 g of ammonium fluoride and 1.502 g of urea were weighed and dissolved in 60 mL of deionized water and stirred for 30 minutes, and the nickel foam treated in (1) was added and reacted in a 100 mL reactor at 100° C. for 6 h. After natural cooling, the mixture was taken out, washed with ethanol and deionized water, and dried at 70° C. for 3 hours;
[0036] (3) The product obtained in (2) was cut into a size of 1 cm*1.5 cm, and then placed in a transparent sample bottle containing 20 mL of a 0.60 g / L aqueous solution of ruthenium trichloride trihydrate, and shaken at 270 r / min for 6 hours in an oscillator at 25°C for ion exchange, and then taken out and washed with deionized water, and then dried at 70°C for 4 hours;
[0037] Comparative Example
[0038] (1) A 1 cm*5 cm nickel foam was placed in a 3 mol / L hydrochloric acid solution for etching for 20 minutes, and then taken out and ultrasonicated with ethanol and deionized water for 15 minutes respectively;
[0039] (2) Weigh 1.454 g of nickel nitrate hexahydrate, 0.556 g of ammonium fluoride and 1.502 g of urea, dissolve in 60 mL of deionized water and stir for 30 minutes, add the nickel foam treated in (1), and react in a 100 mL reactor at 100 ° C for 6 h. After cooling naturally, take out, wash with ethanol and deionized water, dry at 70 ° C for 3 hours, and then cut into 1 cm*1.5 cm pieces;
[0040] 2. Research on the removal of bromate
[0041] (1) The nickel foam loaded Ru-Ni(OH)2 electrode prepared in Examples 1 to 4 and the comparative example was used to treat bromate-containing wastewater, and the specific steps were as follows:
[0042] A simulated water sample consisting of 50 μmol / L sodium bromate and 10 mmol / L sodium sulfate was used, and the pH was adjusted to 5.0. The removal performance of bromate ions by the electrodes prepared in Examples 1 to 4 and the comparative example was studied. 40 mL of the prepared sodium bromate solution was added to a 50 mL electrolytic cell, and the magnetic stirring speed was 300 r / min. The cathode used the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Examples 1 to 4 and the nickel foam electrode loaded with nickel hydroxide in the comparative example, and the anode used a 1.0 cm*1.0 cm platinum sheet electrode. The distance between the cathode and the anode was set to 1.8 cm, and the current density was 10 mA·cm -2 The reaction was carried out at 298.15 K for 90 minutes and samples were taken at required time intervals. Potassium iodide was used as a reducing agent and the bromate concentration was determined by a UV spectrophotometer.
[0043] Table 1 Comparison of the removal effect of bromate at different ruthenium loadings
[0044] Example 1 Example 2 Example 3 Example 4 Comparative Example Time (minutes) Removal rate Removal rate Removal rate Removal rate Removal rate 0 0.00% 0.00% 0.00% 0.00% 0.00% 5 14.40% 18.51% 19.53% 23.98% 4.08% 10 23.99% 30.48% 33.74% 34.91% 5.78% 15 33.60% 41.73% 43.68% 44.08% 7.13% 20 42.86% 51.16% 50.78% 55.36% 8.49% 30 52.80% 64.22% 67.47% 69.82% 9.85% 45 65.84% 73.29% 79.55% 82.51% 11.89% 60 72.35% 79.10% 84.52% 88.86% 16.30% 90 80.59% 83.45% 88.78% 91.33% 20.03%
[0045] As can be seen from Table 1, the removal rate of bromate by the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Examples 1 to 4 and the nickel foam electrode loaded with nickel hydroxide in the comparative example has been greatly improved with the participation of ruthenium. As the initial ruthenium concentration increases when preparing the electrode, the promotion effect of the prepared nickel foam loaded Ru-Ni(OH)2 electrode on the removal of bromate also shows an upward trend, but the upward trend is getting slower and slower. Considering the cost, when the initial ruthenium concentration is 0.6g / L when preparing the electrode, the removal rate of bromate reaches 91.33% within 90 minutes, and the removal effect is significantly improved compared with the 20.03% removal rate of the comparative example.
[0046] 3. Study on the removal of bromate under different current density conditions
[0047] At different current densities, the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 was used to treat bromate-containing wastewater to explore the effect of current density on bromate removal performance. The specific steps are as follows:
[0048] A simulated water sample consisting of 50 μmol / L sodium bromate and 10 mmol / L sodium sulfate was adjusted to pH 5.0. 40 mL of the prepared sodium bromate solution was added to a 50 mL electrolytic cell. The magnetic stirring speed was 300 r / min. Different current densities were set. The reaction was carried out at 298.15 K for 90 minutes, and samples were taken at required time intervals.
[0049] Table 2 Comparison of the removal effect of bromate at different current densities
[0050] <![CDATA[1mA / cm 2 ]]> <![CDATA[2mA / cm 2 ]]> <![CDATA[5mA / cm 2 ]]> <![CDATA[10mA / cm 2 ]]> <![CDATA[15mA / cm 2 ]]> Time (minutes) Removal rate Removal rate Removal rate Removal rate Removal rate 0 0.00% 0.00% 0.00% 0.00% 0.00% 5 2.85% 16.57% 23.37% 24.77% 20.45% 10 5.34% 32.44% 35.24% 34.19% 34.56% 15 8.56% 41.96% 46.05% 45.35% 43.02% 20 10.69% 53.60% 58.26% 57.92% 55.01% 30 18.89% 70.17% 74.32% 69.78% 66.29% 45 28.52% 83.22% 82.00% 80.25% 77.22% 60 38.49% 90.62% 88.97% 86.18% 83.22% 90 55.59% 96.61% 93.51% 90.72% 87.09%
[0051] As can be seen from Table 2, the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 is greatly affected by the current density. With the increase of current density, the effect of the prepared nickel foam loaded Ru-Ni(OH)2 electrode on the removal of bromate shows a trend of first increasing and then decreasing. This is because with the increase of current density, the formation rate of H* is accelerated, the electron transfer is enhanced, and the removal of bromate is promoted. With the further increase of current density, the accumulation of excessive H* may promote the formation and release of hydrogen (Heyrovsky and Tafel reactions), which is not conducive to the removal of bromate. The current density is 2mA / cm 2 When the bromate removal rate was 96.61% within 90 minutes, the removal effect was significant.
[0052] 4. Study on the removal of bromate under different pH conditions
[0053] Under different pH conditions, the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 was used to treat bromate-containing wastewater to explore the effect of pH conditions on bromate removal performance. The specific steps are as follows:
[0054] The simulated water samples were composed of 50 μmol / L sodium bromate and 10 mmol / L sodium sulfate, adjusted to different pH values, and 40 mL of the prepared sodium bromate solution was added to a 50 mL electrolytic cell. The magnetic stirring speed was 300 r / min, and the current density was set to 2 mA cm -2 , react at 298.15 K for 90 min, and take samples at required time intervals.
[0055] Table 3 Comparison of the removal effect of bromate at different pH values
[0056] PH=5.0 PH = 7.0 PH = 9.0 Time (minutes) Removal rate Removal rate Removal rate 0 0.00% 0.00% 0.00% 5 16.57% 14.66% 7.70% 10 32.44% 24.32% 11.91% 15 41.96% 33.62% 18.56% 20 53.60% 42.20% 23.81% 30 70.17% 58.30% 34.33% 45 83.22% 74.39% 50.43% 60 90.62% 82.98% 63.03% 90 96.61% 93.35% 76.33%
[0057] As can be seen from Table 3, the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 is greatly affected by pH. As the pH increases, the effect of the prepared nickel foam loaded Ru-Ni(OH)2 electrode on the removal of bromate shows a downward trend. This is because the increase in pH will inhibit the generation of H*. At the same time, the increase in pH will increase the energy barrier for the breakage of the Br-O bond, thereby reducing the electrocatalytic performance. When the pH is 5, the removal rate of bromate reaches a maximum of 96.61% within 90 minutes, which has a good removal effect.
[0058] 5. Study on the removal of bromate under different initial bromate concentrations
[0059] Under different initial bromate concentration conditions, the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 was used to treat bromate-containing wastewater to explore the effect of the initial bromate concentration conditions on the bromate removal performance. The specific steps are as follows:
[0060] The simulated water samples were composed of 10 μmol / L, 20 μmol / L, 50 μmol / L sodium bromate and 10 mmol / L sodium sulfate, respectively, and the pH was adjusted to 5.0. 40 mL of the prepared sodium bromate solution was added to a 50 mL electrolytic cell, the magnetic stirring speed was 300 r / min, and the current density was set to 2 mA cm -2 , react at 298.15 K for 90 min, and take samples at required time intervals.
[0061] Table 4 Comparison of bromate removal effects at different initial bromate concentrations
[0062]
[0063]
[0064] As can be seen from Table 4, the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 is less affected by the initial bromate concentration. As the initial bromate concentration decreases, the effect of the prepared nickel foam loaded Ru-Ni(OH)2 electrode on the promotion of bromate removal shows a small downward trend. This may be because the utilization rate of the reducing agent (electrons and H*) is reduced during the bromate reduction process, thereby reducing the electrocatalytic performance. However, at all initial concentrations, the removal rate of bromate reached more than 90%, which has great practical application potential.
[0065] 6. Electrode stability study
[0066] The stability of the electrode is a key indicator for formal use. In the process of electrocatalytic reduction of bromate, the electrode was reused 5 times to compare the removal efficiency of bromate to evaluate the stability of the nickel foam loaded Ru-Ni(OH)2 electrode. The specific steps are as follows:
[0067] The simulated water sample was composed of 50 μmol / L sodium bromate and 10 mmol / L sodium sulfate, and the pH was adjusted to 5.0. The removal performance of the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 on bromate was studied. 40 mL of the prepared sodium bromate solution was added to a 50 mL electrolytic cell, the magnetic stirring speed was 300 r / min, and the current density was 2 mA·cm -2 , reacted at 298.15K for 90 minutes, and samples were taken at required time intervals. After the experiment was completed, the electrode was washed with water, dried at 60℃, and then used for repeated experiments.
[0068] Table 5 Comparison of the removal effect of bromate at different repetition cycles
[0069] Cycle 1 Cycle 2 Cycle 3 Cycle 4 Cycle 5 Removal rate 93.42% 88.94% 87.45% 85.96% 85.21%
[0070] It can be seen from Table 5 that the removal effect of the nickel foam loaded Ru-Ni(OH)2 electrode prepared in Example 4 on bromate slowly decreases with the increase of repeated cycles, from the initial 93.42% to 85.21% in the fifth cycle. This is mainly because as the use time increases, the electrode will lose some active substances and the removal performance will decrease.
Claims
1. A method for preparing a nickel foam loaded Ru-Ni(OH)2 electrode with high catalytic performance, characterized in that: The following steps are involved: (1) placing the initial nickel foam support in a hydrochloric acid / sulfuric acid / nitric acid solution with a molar concentration of 3 mol / L for ultrasonic etching to remove impurities and oxide film on the surface of the nickel foam, and then ultrasonically etching with ethanol and deionized water for 10-15 minutes respectively; (2) the nickel foam in step (1) is placed in a homogeneous solution of nickel nitrate hexahydrate, ammonium fluoride and urea, and subjected to a hydrothermal reaction at 90-120° C., wherein the nickel nitrate hexahydrate serves as a nickel source, and the ammonium fluoride and urea provide an alkaline environment for the reaction and promote the formation of a specific crystal structure. After the reaction is completed, the nickel foam is taken out and washed with ethanol and deionized water, and dried at 70° C. for 2-4 hours to obtain a nickel foam loaded with nickel hydroxide; (3) Immersing the nickel foam loaded with nickel hydroxide in step (2) in a ruthenium trichloride solution to exchange ruthenium ions with nickel hydroxide, after which the electrode is taken out, washed with water, and dried at 70° C. for 3-5 hours to obtain a nickel foam loaded Ru-Ni(OH)2 electrode.
2. The method for preparing a foam nickel-loaded Ru-Ni(OH)2 electrode with high catalytic performance according to claim 1, characterized in that: In step (1), the etching time of the nickel foam carrier in the hydrochloric acid solution is 10 to 20 minutes.
3. The method for preparing a foam nickel-loaded Ru-Ni(OH)2 electrode with high catalytic performance according to claim 1, characterized in that: In step (2), the mass ratio of nickel nitrate hexahydrate, ammonium fluoride and urea is 0.466-1.454: 0.178-0.556: 0.481-1.
502.
4. The method for preparing a foam nickel-loaded Ru-Ni(OH)2 electrode with high catalytic performance according to claim 1, characterized in that: In step (2), the hydrothermal reaction time is 4-8 hours.
5. The method for preparing a nickel foam loaded Ru-Ni(OH)2 electrode with high catalytic performance according to claim 1, characterized in that: In step (3), the concentration of ruthenium trichloride is 0.05 to 0.60 g / L.
6. The method for preparing a foam nickel-loaded Ru-Ni(OH)2 electrode with high catalytic performance according to claim 1, characterized in that: In step (3), the ion exchange time is 2-6 hours.
7. Use of the nickel foam loaded Ru-Ni(OH)2 electrode prepared according to the preparation method according to claims 1-6 in the treatment of bromate-containing wastewater.
Citation Information
Patent Citations
Method for removing perchlorate from water body through electrochemical reduction
CN107162117A
Preparation method of iron-based tellurium / oxide heterojunction supported ruthenium catalyst and application of iron-based tellurium / oxide heterojunction supported ruthenium catalyst in seawater electrolysis hydrogen production
CN117845268A
Cathode for electrochemical filtration, electrochemical filter and application thereof
CN117886403A
Preparation method of transition metal doped ruthenium-nickel hydroxide composite catalyst
CN118028889A
Ruthenium-nickel / activated carbon co-supported catalyst, preparation thereof and use thereof
WO2020114287A1